2020
DOI: 10.1101/2020.09.29.319103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stability landscape ofde novoTIM barrels explored by a modular design approach

Abstract: The design of stable proteins with custom-made functions is a major goal in biochemistry with practical relevance for our environment and society. High conformational stability lowers protein sensitivity to mutations and changes in the environment; thus, understanding and manipulating protein stability will expand the applications of de novo proteins. Since the (β/α)8-barrel or TIM-barrel fold is one of the most common functional scaffolds, in this work we designed a collection of stable de novo TIM barrels (N… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Sequence overlap between TIM-barrel subunits for model TIM-barrel designs (orange) and previously characterized sequences for the same scaffold (blue), including sTIM-11 (5bvl, S11) [40], DeNovoTIM15 (6wvs, D15) [44], and NovoTIMs (N6, N13, N14a, N14b) [45]. Specific overlaps shown for the region between ( A ) the helices and the barrel, ( B ) the inner part of the barrel, ( C ) exposed regions, and ( D ) all residues.…”
Section: Supplementary Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence overlap between TIM-barrel subunits for model TIM-barrel designs (orange) and previously characterized sequences for the same scaffold (blue), including sTIM-11 (5bvl, S11) [40], DeNovoTIM15 (6wvs, D15) [44], and NovoTIMs (N6, N13, N14a, N14b) [45]. Specific overlaps shown for the region between ( A ) the helices and the barrel, ( B ) the inner part of the barrel, ( C ) exposed regions, and ( D ) all residues.…”
Section: Supplementary Textmentioning
confidence: 99%
“…( B ) Distribution of rotamer automorphic RMSDs (Å) between crystal structure and template backbone for core and solvent-exposed residues for (top) F2C and (bottom) F15C. ( C ) Sequence overlap between TIM-barrel subunits for model TIM-barrel designs (orange) and previously characterized sequences for the same scaffold (blue), including sTIM-11 (5bvl, S11) [40], DeNovoTIM15 ( 6wvs , D15) [44], and NovoTIMs (N6, N13, N14a, N14b) [45]. Edge thickness increases with overlap.…”
mentioning
confidence: 99%
“…We further introduced a small change to the sTIM11 scaffold by removing two cysteine residues that were originally introduced to form a disulfide bridge to improve barrel closure 9 . However, this disulfide bond did not form, so we removed the two cysteines to generate a cysteine‐free variant named sTIM11noCys whose characteristics and crystal structure are reported in Romero‐Romero et al 12 …”
Section: Resultsmentioning
confidence: 99%
“…Further analysis revealed a significantly lower conformational stability compared to natural TIM barrels. In a modular approach, a collection of stabilized variants (DeNovoTIMs) was designed by improving hydrophobic packing [ 86 •• ]. Structural and folding analysis showed that epistatic effects allow navigating an unexplored region of the stability landscape of natural proteins.…”
Section: Learning From Nature Towards Protein Designmentioning
confidence: 99%